Effect of Exercise-Induced Reductions in Blood Volume on Cardiac Output and Oxygen Transport Capacity - Schierbauer, Janis; Hoffmeister, Torben; Treff, Gunnar; Wachsmuth, Nadine B.; Schmidt, Walter F. J. (Frontiers in Physiology, 2021)
OBJECTIVE: To demonstrate the relationship between blood volume and cardiac size, cardiac output and maximum oxygen uptake (V̇O2max) and to quantify blood volume shifts during exercise and their impact on oxygen transport. METHODS: Twenty-four healthy, nonsmoking, heterogeneously trained male participants (27±4.6 ys) performed incremental cycle ergometer tests to determine V̇O2max and changes in blood volume and cardiac output. Cardiac output was determined by an inert gas rebreathing procedure. Heart dimensions were determined by 3D echocardiography. Blood volume and hemoglobin mass were determined by using the optimized CO-rebreathing method. RESULTS: V̇O2max ranged between 47.5 and 74.1 mL·kg-1·min-1. Heart volume ranged between 7.7 and 17.9 mL·kg-1 and maximum cardiac output ranged between 252 and 434 mL·kg-1·min-1. The mean blood volume decreased by 8% (556±187 mL, p=0.001) until maximum exercise, leading to an increase in [Hb] by 1.3±0.4 g·dL-1 while peripheral oxygen saturation decreased by 6.1±2.4%. There were close correlations between resting blood volume and heart volume (r=0.73, p=0.002), Maximum blood volume and maximum cardiac output (r=0.68, p=0.001), and maximum cardiac output and V̇O2max (r=0.76, p<0.001). An increase in maximum blood volume by 1000 mL was associated with an increase in maximum stroke volume by 25 mL and in maximum cardiac output by 3.5 L·min-1. CONCLUSION: Blood volume markedly decreased until maximal exhaustion, potentially affecting the stroke volume response during exercise. Simultaneously, hemoconcentrations maintained the arterial oxygen content and compensated for the potential loss in maximum cardiac output. We therefore conclude that a large blood volume at rest is an important factor for achieving a high cardiac output during exercise and that blood volume shifts compensate for the decrease in peripheral oxygen saturation, thereby maintaining a high arteriovenous oxygen difference.